Ultrasound derived measurements ability to predict max aerobic performance - Sobolewski, E. J.; Carpenter, K. M.; Rodriguez, G. C.; Hall, A. B.; Richard, M. O. (International Journal of Sport & Health Science, 2021)
The purpose of this study was to determine the relationship between EI, CSA, and aerobic performance, and to develop a model to predict aerobic performance. Twenty aerobically trained participants had a panoramic ultrasound taken of their rectus femoris and vastus lateralis muscles on their right leg before performing a maximal aerobic cycling test. Ultrasound derived echo intensity and cross-sectional area were compared to peak oxygen consumption (VO2) and maximal power output. Pearson`s product coefficients were used to determine the relationship between ultrasound measurements and aerobic performance values, while a multiple regression model was used to determine what indicators predict in maximal VO2 and max watt output. Results indicated a significant negative relationship between echo intensity (p<0.05) for max power and VO2 and a positive relationship with cross-sectional area (p<0.05) for max power and VO2. Stepwise regression revealed that muscle echo intensity, cross-sectional area, and sex were good predictors of both max Power and VO2. These findings demonstrate that higher quality muscle values (lower echo intensity) and larger muscle size have a higher aerobic performance output than smaller lower quality muscle.